The War in the Pacific - Horan Don; Zimmermna, Morth; History Channel (Television network).; A&E Home Video (Firm).; New Video Group (New York A & E Television Networks, 1983)
From the horrifyng attack on Pearl Harbor and the bloddy island-hopping campaign through the Pacific to the atomic bombing of Japan and the surrender on the deck of the U.S.S. Missouri, this nearly two-and-a-half hour presentation is the most comprehensive video produced on the war in the pacific.
With 2 converted discs.
Executive producer, Lou Reda.
VHS format.
In English.
Keywords: World War, 1914-1918.; World War, 1939-1945.